A Way to Estimate Hydraulic Quantities and Basic Characteristics of Inundated Flow with Floating Bodies - MATSUTOMI, Hideo; FURUTO, Takahiro (PROCEEDINGS OF COASTAL ENGINEERING, JSCE, 2008)
A method for estimating basic hydraulic quantities of inundated flow with floating bodies in the hydraulic experiments is presented and its validity is confirmed through examining quasi-steadiness of the flow, consistency among inundation depth of the flow, current velocity of the flow and void ratio of layer having floating bodies, and so on. Using the experimental data estimated by the presented method, applicability of the existing theory for estimating the moving velocity of floating bodies, i.e., the current velocity of inundated flow with floating bodies is examined, and it is concluded that the theory is useful in a practical situation. Fundamental characteristics of the inundated flow with floating bodies are also discussed through examinations of the experimental results and solutions of the theory.